PERSEPSI KELUARGA TERHADAP FAMILY ENGAGEMENT PADA KELUARGA PASIEN DI RUANG PERAWATAN INTENSIF - Fadhia Syaharani Ardira (2023)
The provision of health services in the intensive care unit does not only focus on family care but engages the patient's family as a companion in the process. The phenomenon of family and health professional engagement is a relationship and interaction that is of concern in the process of continuity of care. This study aims to describe family perceptions of family engagement of patient families in the intensive care unit. The research design used a qualitative descriptive study that focused on revealing the family's perception of family engagement while undergoing treatment in the ICU. The samples in this study were 10 patient families using a snowball sampling technique.The themes found in this study are 1) Patient Care Supplement on Family Engagement 2) ICU Visiting System as a Referral for Patient's Family Arrival 3) Effectiveness of the Communication Process as an Integrated Care Approach in the ICU 4) Shared Decision-Making Process in the Form of Family Guidelines in the ICU 5) Providing Support and Attitudes of Health Professionals to Families. Establishing family engagement provides benefits to both families and health professionals in care. Therefore, this study can be a foundation for further research on the topic of family engagement, which is still limited.